The alcohol marker phosphatidylethanol is closely related to AST, GGT, ferritin and HDL‐C. Issue 1 (26th October 2021) - Høiseth, Gudrun; Hilberg, Thor; Trydal, Torleif; Husa, Asgeir; Vindenes, Vigdis; Bogstrand, Stig Tore
Abstract: Background: The aim of this study was to evaluate the quantitative relation between common clinical chemical analyses and ethanol use, measured by a combination of the two alcohol markers phosphatidylethanol (PEth) and carbohydrate‐deficient transferrin (CDT). Methods: Results of PEth and CDT in whole blood and serum, respectively, were included, together with information on 10 different commonly measured clinical chemical analytes, as well as age and sex. PEth was analysed by UPC 2 ‐MS/MS and CDT was measured by capillary electrophoresis. Results: Samples from 4873 patients were included. The strongest relation to alcohol consumption as measured by PEth, when correcting for age and sex, was found for HDL‐C (standardized β = 0.472, p  < 0.001), AST (standardized β = 0.372, p  < 0.001), ferritin (standardized β = 0.332, p  < 0.001) and GGT (standardized β = 0.325, p  < 0.001). The relation to PEth was weak for total cholesterol, TG and ALP. No relation was found for Hb and LDL‐C. Conclusions: When using PEth as a marker for alcohol consumption, this study demonstrated the quantitative relation to commonly used test as AST or GGT, but also an important relation to ferritin or HDL‐C. In clinical practice, elevated levels of these clinical chemical analytes should initiate further work‐up on possibly harmful alcohol use.